Música, retórica e leitura: a mulher na MPB e a constituição do ethos feminino - Lyra, Elizabeth Rizzi (2018)
This work is part of the research line “Reading, Writting and Portuguese Language Teaching”, from the Postgraduate Program in Portuguese Language of the Pontifical Catholic University of São Paulo. It has as general objective, the constitution of the female ethos in songs written by women composers, as well as the reading, from the rhetorical perspective of those songs in the learning environment of a regular school. Therefore, we have analyzed the female participation in the music history and the application of musical genre in the formation of youth education since the Old Greece back to current days. Based on the theoretical concepts, we analyze the songs Resposta (1958) from Maysa, Essa mulher (1978) composed by Joyce feat Ana Terra and Pagu (2000) from Rita Lee, so we could analyze which rhetorical appeals are applied in the constitution of the ethos of the woman. We highlighted through this analysis, the related aspects to the ethos (the composer’s credibility) and the logos (arguments and figures), just as the pathetic effects awakened in the audience by those songs. The ethos of the resistance and the manifestation of the passion for so long repressed, strongly uncovers in the songs. Regarding the reading in class, we can assure that the songs become rich sources in the formation of competent readers